Plasticizers as Microplastics Tracers in Tunisian Marine Environment - Gugliandolo, Enrico; Licata, Patrizia; Crupi, Rosalia; Albergamo, Ambrogina; Jebara, Amel; Lo Turco, Vincenzo; Potortì, Angela Giorgia; Mansour, Hedi Ben; Cuzzocrea, Salvatore; Di Bella, Giuseppa (Frontiers in Marine Science, 2020)
The new knowledge on the bio-transformations to which the plastic material is subjected, raise concerns about their role as environmental contaminants. Microplastic have been reported to be responsible for the release and distribution of aquatic contaminants such organophosphorus esters, pesticides, polycyclic aromatic hydrocarbons, polychlorinated biphenyls, and phthalate esters. The occurrence, spatiotemporal trends, and ecological risk of phthalic acid esters (PAEs) and non-phthalate plasticizers (NPPs) released from microplastic were investigated in water and fish (Sparus aurata) from five sites along the coast of Mahdia governorate (Tunisia), during April 2018-March 2019. In seawater the most abundant and frequently detected congeners were dibutyl phthalate (DBP, 0.017 mg L–1 and 0.055 mg L–1), diisobutyl phthalate (DiBP, 0.075 mg L–1 and 0.219 mg L–1), di(2-ethylhexyl)phthalate (DEHP, 0.071 mg L–1 and 4.594 mg L–1), and di(2-ethylhexyl) terephthalate (DEHT, 0.634 mg L–1 and 2.424 mg L–1). (ΣPAEs: 1.416 mg L–1 and 5.581 mg L–1; ΣNPPs: 9.191 mg L–1 and 26.296 mg L–1), confirming that such compounds bioconcentrate through the food chain. DBP (0.389 and 0.817 mg L–1), DiBP (0.101 and 0.921 mg L–1), DEHP (0.726 and 1.771 mg L–1) and DEHT (9.191 and 23.251 mg L–1) were predominant also in S. aurata affirming that such compounds bioconcentrate through the food chain. Overall, Tunisian samples i) were much more contaminated than counterparts previously investigated for the same pollutants from other world areas, and ii) revealed NPPs at higher levels than PAEs, confirming that such plasticizers are increasingly replacing conventional PAEs.